Response to atrial overdrive pacing during narrow QRS tachycardia. What is the mechanism? - Suchit Majumdar (Indian Pacing and Electrophysiology Journal, 2020)
A 35-year old lady with no pre-excitation on surface electrocardiogram underwent EP study for recurrent palpitation and documented adenosine responsive narrow QRS tachycardia. Regular narrow QRS tachycardia was induced with critical AH delay on programmed atrial stimulation. An atrial overdrive pacing (AOD) was performed during the tachycardia (Fig: 1 & 2). What is the response to AOD and what is the mechanism of tachycardia?